RNase reverses segment sequence in the anterior of a beetle egg (Callosobruchus maculatus, Coleoptera) - Meer, Jitse M. van der (Journal of experimental zoology. Part B, Molecular and developmental evolution, 2018)
The genetic regulation of anterior-posterior segment pattern development has been elucidated in detail for Drosophila, but it is not canonical for insects. A surprising diversity of regulatory mechanisms is being uncovered not only between insect orders, but also within the order of the Diptera. The question is whether the same diversity of regulatory mechanisms exists within other insect orders. I show that anterior puncture of the egg of the pea beetle Callosobruchus maculatus submerged in RNase can induce double abdomen development suggesting a role for maternal mRNA. In a double abdomen, anterior segments are replaced by posterior segments oriented in mirror image symmetry to the original posterior segments. This effect is specific for RNase activity, for treatment of the anterior egg pole and for cytoplasmic RNA. Yield depends on developmental stage, enzyme concentration, and temperature. A maximum of 30% of treated eggs reversed segment sequence after submersion and puncture in 10 μg/mL RNase S reconstituted from S-protein and S-peptide at 30°C. This result sets the stage for an analysis of the genetic regulation of segment pattern formation in the long germ embryo of the coleopteran Callosobruchus and for comparison with the short germ embryo of the coleopteran Tribolium.